International norm polarization: sexuality as a subject of human rights protection. Issue 1 (9th February 2015) - Symons, Jonathan; Altman, Dennis
<x content-type="archive" xml:space="preserve">Abstract</x> International norm polarization is a rare but recurring process within international norm dynamics. Polarization describes the most combative response to attempted norm change: 'a candidate norm is accepted by some states but resisted by others, leading to a period of international disputation between two groups in which socializing pressures pull states toward compliance with rival norms'. We identify several cases of polarization and explain this phenomenon by elaborating the constructivist model of the norm life cycle to processes of international resistance to norm change as well as to norm acceptance. We also draw on social identity theory (SIT) to examine group-psychological responses where disputed norms become closely linked to state identity. We illustrate these dynamics with reference to conflict over the norm that recognizes sexual orientation and gender identity as subjects of international human rights protection. Over the past decade this candidate norm has become increasingly contentious internationally, and bitter debates over resolutions concerning extra-judicial killings and discrimination have divided the United Nations General Assembly and Human Rights Council. The article makes a primary contribution to analysis of international norm change and also contributes to an emerging literature concerning sexuality and international relations.